PRESSURE SOURCE ESTIMATION OF SINABUNG VOLCANO BASED ON CONTINOUS GPS DATA APRIL 2011 ÃâÃâ SEPTEMBER 2015 PERIOD - ERA PAMITRO (NIM: 22413014); Tim Pembimbing: Dr. Irwan Meilano, M.Sc.; Dr. Estu Kriswati, M.Sc, YOGA
Eruption activity of a volcano is usually preceded by some precursors such as an increase in seismic activity, an increase in the temperature of the hot springs, changes in the composition and strength of gas emmisions, as well as deformation of the volcano. To be able to monitor the activity of a volcano, it is important to consider data input from a wide variety of monitoring methods, one of these methods is deformation monitoring using GPS data. This study conducted deformation analysis of Sinabung Volcano based on GPS data processed by GAMIT/GLOBK 10.6 software, and then also modeling using dMODELS software to determine the depth and volume changes at pressure source. The data used in this study is including local data from continuous GPS observation stations owned by PVMBG (Center for Volcanology and Geological Hazard Mitigation) around Sinabung Volcano. There is also one additional continuous GPS station owned by BIG (Geospatial Information Agency). While the IGS stations used as a tie point in analyzing the displacement time series against the ITRF 2008 are as many as 10 stations. The depth of the pressure source modeling results indicate some possibilities that Sinabung has a deep magma chamber (about 14-21 km under the surface) and also shallow magma chamber (about 4 km under the surface).